1991
DOI: 10.1042/bst0190368
|View full text |Cite
|
Sign up to set email alerts
|

Stretch and force generation induce rapid hypertrophy and myosin isoform gene switching in adult skeletal muscle

Abstract: Using electrical stimulation to control force generation and limb immobilization to alter the degree of stretch, we have studied the role of mechanical activity in inducing hypertrophy and in determining fast and slow muscle fibre phenotype. Changes in gene expression were detected by analysing the RNA in hybridization studies employing cDNA probes specific for fast and slow myosin heavy chains and other genes. As a result of overload in the stretched position, the fast contracting tibialis anterior muscle in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 4 publications
3
50
0
Order By: Relevance
“…For example, chronic immobilization of the rabbit ankle in plantar flexion resulted in a 20% increase in the dorsiflexor muscles after only three to four days. 29,32 Casting muscles in lengthened positions results in similar hypertrophic and functional changes seen in avian stretch and rodent ablation and tenotomy overload models. 75 It is interesting to note that studies have also shown that combinations of muscle stretch and muscle activity induced by electrical stimulation result in a 10% greater increase in muscle mass compared to stretch alone.…”
Section: Chronic Stretch Modelsmentioning
confidence: 99%
“…For example, chronic immobilization of the rabbit ankle in plantar flexion resulted in a 20% increase in the dorsiflexor muscles after only three to four days. 29,32 Casting muscles in lengthened positions results in similar hypertrophic and functional changes seen in avian stretch and rodent ablation and tenotomy overload models. 75 It is interesting to note that studies have also shown that combinations of muscle stretch and muscle activity induced by electrical stimulation result in a 10% greater increase in muscle mass compared to stretch alone.…”
Section: Chronic Stretch Modelsmentioning
confidence: 99%
“…Similar findings were observed after general sprint training (3), as expressed by a decrease in the number of individual fibers that expressed MHC-IIB. Indeed, it has been suggested that MHC-IIB is the ''default'' gene (21), the expression of which is increased with disuse and ''switches'' to MHC-IIA when activity is increased (5). In the present study MHC-IIB was detected in the vastus lateralis in only four of the subjects, an observation that possibly reflects a relatively high level of habitual physical activity in our subjects, although none was sprint trained or strength trained.…”
mentioning
confidence: 99%
“…A factor that should also be considered is the duration of the stimulus required for transformation [96]. In adult animals, changes have been observed even after extremely short periods of stimulation [48].…”
Section: Series 'Cell Biology Of Respiratory Muscles' Edited By M Dementioning
confidence: 99%
“…It is believed that the expression is regulated fundamentally by mechanical signals, particularly by changes in the tension generated by the muscle during the effort [47]. The stretch (active tension) as well as electrical stimulation (passive tension) provoke the repression of the fast-type genes, with activation of the slow-type genes [2,48]. This implies a progressive transformation in the type of fibres [49][50][51][52].…”
Section: Series 'Cell Biology Of Respiratory Muscles' Edited By M Dementioning
confidence: 99%